Introduction to digital mobile communication - Akaiwa, Yoshihiko (Hoboken, New Jersey : Wiley, 2015)
"This book emphasizes digital transmission methods. Beginning with an introduction to what digital mobile communication is, it presents mathematical analyses of signals, mobile radio channels,and digital modulation methods"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Mobile communication systems; Digital communications; TECHNOLOGY & ENGINEERING / Mobile & Wireless Communications; Digital communications; Mobile communication systems; Electronic books; Electronic books